Six-minute walk distance in healthy subjects: reference standards from a general population sample - Cazzoletti, Lucia; Zanolin, Maria Elisabetta; Dorelli, Gianluigi; Ferrari, Pietro; Dalle Carbonare, Luca Giuseppe; Crisafulli, Ernesto; Alemayohu, Mulubirhan Assefa; Olivieri, Mario; Verlato, Giuseppe; Ferrari, Marcello (Respiratory research, 2022)
Introduction The 6-min walking distance (6MWD) test is a useful tool to obtain a measure of functional exercise capacity. However, reference equations have been mainly based on selected populations or small samples. The purpose of this study was to determine the reference equations to predict the 6MWD in a large Italian population sample of healthy adults of a wide age range. Methods In the frame of the multi case–control population-based study Gene Environment Interaction in Respiratory Diseases (GEIRD), we studied 530 healthy subjects: 287 females ranging 21–76 and 243 males ranging 21–78 years of age. We measured 6MWD, demographic and anthropometric data and collected the reported physical activity. A multiple linear regression model for the 6MWD included age, age 2 , height, weight and physical activity for both sex equations. The two-way interaction age-height and age-weight and the quadratic terms of weight and height were also tested for inclusion separately in each model. Results The mean ± SD for 6MWD was 581.4 ± 66.5 m (range 383–800 m) for females and 608.7 ± 80.1 m (range 410–875 m) for males. The reference equations were 6MWD = 8.10*age + 1.61*height cm −0.99*weight kg + 22.58*active−0.10*age 2 + 222.55 for females (R squared = 0.238) and 6MWD = 26.80*age + 8.46*height cm −0.45*weight kg −2.54*active−0.06*age 2 −0.13*age*height cm −890.18 for males (R squared = 0.159), where “active” is 1 when the subject is physically active, 0 otherwise. Conclusion This study is the first to describe the 6MWD in a large population sample of young, middle aged and elderly healthy Caucasian subjects, and to determine reference equations. These findings will help to improve the evaluation of Italian and European patients with diseases influencing their functional capacity.